IMPROVING TEACHERS’ PERFORMANCE THROUGH THE HEADMASTERS’ TRANSFORMATIONAL LEADERSHIP AND MOTIVATION AT PUBLIC ELEMENTARY SCHOOLS - Harkati; Sukirman; Gunawan Setiadi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to analyze the effect of headmasters’ transformational leadership on teachers’ performance, the effect of work motivation on teachers’ performance, and the simultaneous influence of headmasters’ transformational leadership and work motivation on teachers’ performance. This research was conducted in public elementary schools in Kecamatan Tayu, Kabupaten Pati. The study employed a quantitative correlational research design. The sample consisted of 144 respondents. Data were collected using questionnaires distributed to teachers. The data were then analyzed through validity and reliability testing, classical assumption tests, and multiple linear regression analysis, which were processed using IBM SPSS version 24. The results of the study indicated that: (1) headmasters’ transformational leadership (X1) had a significant effect on teachers’ performance in public elementary schools in Kecamatan Tayu, Kabupaten Pati; (2) work motivation (X2) had a significant effect on teachers’ performance in public elementary schools in Kecamatan Tayu, Kabupaten Pati; and (3) headmasters’ transformational leadership and work motivation simultaneously had a significant effect on teachers’ performance in public elementary schools in Kecamatan Tayu, Kabupaten Pati, accounting for 77.6% of the variance in teachers’ performance.